2019
DOI: 10.1038/s41387-019-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training improves hepatic and muscle insulin sensitivity, but reduces splanchnic glucose uptake in obese humans with type 2 diabetes

Abstract: Background Aerobic exercise training is known to have beneficial effects on whole-body glucose metabolism in people with type 2 diabetes (T2D). The responses of the liver to such training are less well understood. The purpose of this study was to determine the effect of aerobic exercise training on splanchnic glucose uptake (SGU) and insulin-mediated suppression of endogenous glucose production (EGP) in obese subjects with T2D. Methods Participants included 11 obese hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Fitness has been shown to play an important role in protecting against glucose intolerance [ 43 ]. This may be related to the well-known effect of muscle contractile activity, hence exercise training, on insulin sensitivity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fitness has been shown to play an important role in protecting against glucose intolerance [ 43 ]. This may be related to the well-known effect of muscle contractile activity, hence exercise training, on insulin sensitivity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the percent of the oral glucose taken up by the splanchnic tissues increased from 38 to 50% within the collapsed group. In a more recent study, Gregory et al ( 50 ) studied the effect of 15 weeks of aerobic exercise training without weight loss (70% VO 2 max, 4–5 days/week, 50 min/day) on SGU in patients with T2D. In addition to observing that insulin-mediated suppression of EGP was improved in the same group of patients after exercise training, it was reported that SGU in response to a 75-gram oral glucose load decreased from 23 grams to 9 grams.…”
Section: Impact Of Exercise On Post-prandial Hepatic Glucose Metabolimentioning
confidence: 94%
“…In addition to the previously noted results by Bogardus et al ( 43 ), Segal et al ( 45 ) observed that fasting HGP was lower in patients with T2D after 12 weeks of aerobic exercise training (4x/week, 1 h/day, 70% VO 2 max) without weight loss. On the other hand, most other studies in patients with T2D that used aerobic exercise training durations of 6 weeks or more report that fasting EGP does not change ( 46 , 48 50 ), even those that incorporate significant weight loss into their study design ( 48 , 49 ). The reason for this discrepancy is not entirely clear, but this is not to say that subjects with T2D from these latter studies did not demonstrate improved hepatic function as a result of exercise training.…”
Section: Impact Of Exercise On Fasting Hepatic Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…A portion of the regulation of glucagon secretion has been ascribed to an inhibitory effect of insulin on glucagon secretion, also known as the intra-islet hypothesis (14,15). In fact, the intravenous (IV) infusion of insulin during euglycemia has been shown to lower glucagon levels in dogs (16), healthy humans (17)(18)(19)(20), and patients with diabetes (21)(22)(23). In contrast, endogenous insulin secretion, such as occurs after a meal, does not have the same inhibitory effect on glucagon levels (24), thereby raising the possibility that endogenous insulin regulates glucagon secretion differently than IV insulin.…”
Section: Introductionmentioning
confidence: 99%